A Patient’s Tale of Incarceration in a Victorian Lunatic Asylum - Berkencotter, Carol (International Journal of English Studies, 2011)
Using the archival admissions records and the case history of a patient at a British asylum in the 1870s, the author compares two genres. The first of these is two medical certificates written and signed by two physicians attesting that the patient was of unsound mind and needed to be confined and treated. The second genre is the patient’s oral testimony to Parliament’s Select Committee on Lunacy Laws (1877), a narrative he delivered the year following his release from the asylum. Both genres are legal texts; however, it is the patient’s narrative of personal experience, as transcribed in the committee report, that allows the reader a glimpse of the misery imposed by confinement in a “lunatic” asylum. The two medical certificates have considerably more illocutionary force, however; as speech acts they most often resulted in confinement until the patient was determined to have recovered, was transferred to another asylum, or died.